‘Come on mate, let's make you a cup of tea’: Theorising materiality and its impacts on detainee dignity inside police detention - Skinns, Layla (Theoretical criminology, 2024)
In this article, we examine detainee experiences of dignity in police detention through the lens of materiality. To do this, we draw on sociological and anthropological literature on the ‘material turn’ and its application to criminal justice settings, and a mixed-methods study of police custody in England and Wales. First, we conceptualise different dimensions of materiality in police custody. Second, we show how some forms of materiality, in conjunction with staff–detainee relationships, shape detainee dignity rooted in equal worth, privacy and autonomy. Third, we examine how the intertwining of the social and material in police custody opens up new possibilities for theorising police work. The materiality of police work is active, not just symbolic. Alongside social relations, it shapes citizen experiences of the police, including of ‘hard’ and ‘soft’ forms of policing, and by implication, pain and injustice. Materiality therefore provides a further way of theorising the production of social order inside and outside police detention.